PRODUK DOMESTIK REGIONAL BRUTO PER KAPITA DAN PEMBANGUNAN EKONOMI YANG INKLUSIF DAN BERKEADILAN DI KABUPATEN TOBA SAMOSIR - Sihaloho, Henrykus (UNIKA Santo Thomas, 2015)
Abstract The goals of this research were to acquire overview of Regional Domestic Product (GRDP) per capita and to design inclusive and righteous economic growth (growth with equity). Toba Samosir Regency’s Gross Regional Domestic Product (GRDP) per capita at Current Market Prices 2000 in 2013 was increasing every year, meanwhile GRDP per capita in 2009-2013 at Constant Market Prices 2000 showed the economic growth increased significantly in Toba Samosir Regency and North Sumatera Province. In order to actualize inclusive and righteous economic growth in Toba Samosir Regency, the government of this regency will have to introduce mina-rice (fish-paddy) programme. Introducing thia programme with labor intensive will be potential to increase income and to provide job opportunities labor occasion as well as ti decrease overloaded fish nurture. The government of Toba Samosir Regency should invite investors to build some feed industries of corn-soybean meal.